Recurso de embargos infringentes - Rodrigues, Fernando Anselmo (2007)
The object of this work is specifically the analysis of the historic evolution of the. It is a very controvertial matter, that has a undeniable importance. To the analysis of the peculiarities of this appeal and the hipothesys of, a previous study has been made as a way of the court decision. The in our civil procedual system is very important the position of some should be considered, and they think that the should be abolished of our system, even more the end of the process, desconsidering the existence of many cases in which errors has been corrected and notorious unjustices reverted in this point of the process